Polarization Multiplexing Hologram Realized by Anisotropic Digital Metasurface. Issue 6 (25th April 2021) - Yan, Tao; Ma, Qian; Sun, Shi; Xiao, Qiang; Shahid, Iqbal; Gao, Xinxin; Cui, Tie Jun
Abstract: Metasurface holograms have the potential to be applied in a variety of practical fields. Here an anisotropic digital metasurface is proposed that can project polarization multiplexing patterns at the microwave frequency, in which a modified Gerchberg–Saxton algorithm is presented to calculate the phase masks. A 3‐bit coding metamaterial unit is also proposed, which is capable of independently manipulating the transmission phases of orthogonal linearly polarized electromagnetic waves. The influence of wave‐front has been analyzed by comparing two holographic results with distinct source optimization methods. A prototype of the anisotropic digital coding metasurface optimized with horn wave‐front is designed, manufactured, and tested. The experimental measurements present the expected holographic fields and have a good match with the simulation results. Abstract : This paper discusses the design of an anisotropic metasurface to form a polarization multiplexing hologram at the microwave frequency. A modified Gerchberg–Saxton algorithm considering the situation of incident wave‐front is designed to determine the transmission phase profile of the metasurface. The 3‐bit metasurface unit cell has been carefully designed to apply the desired phase shift independently in orthogonal polarizations.